Creative Dance Improves Physical Fitness and Life Satisfaction in Older Women - Cruz-Ferreira, A. (2015)
Aim. It has been shown by many authors that proprioception declines with age. However, few studies have examined the effects of exercise interventions on proprioception. The purpose of this study was to investigate the effects of a creative dance program on proprioception of older adults. Methods. Thirty-seven men and women between 55 and 80 years of age, who were not engaged in any exercise program for at least one year, were randomly assigned to an experimental (63.6±5.7 years) or a control group (65.3±7.6 years). The exper- imental group participated in a creative dance program for 12 weeks with a periodicity of 3 sessions of 90 minutes per week. Measures of knee kinesthesia, knee joint position sense and arm positioning were taken before and after the program. Results. After 12 weeks, knee joint position sense (P=0.005) knee kinesthesia (in flexion) (P=0.04), and arm positioning (P=0.008) significantly improved within the creative dance training group. At 12 weeks follow-up, arm positioning per- formance was significantly better for the creative dance group when compared with the control group (P=0.043). The control group did not show any significant improvement in proprio- ception. Conclusion. This study showed that a creative dance program emphasising body awareness can improve proprioception in older adults.